ANALISIS PENENTUAN LOKASI RAWAN KECELAKAAN LALU LINTAS DENGAN METODE BATAS KONTROL ATAS (BKA) BERBASIS GEOGRAPHIC INFORMATION SYSTEM (GIS) DI KABUPATEN LOMBOK TENGAH - ROHANI ROHANI; HASYIM HASYIM; ZIYAD PIRJATURROFI (Universitas Mahasaraswati K. Mataram, 2024)
Traffic accidents are events that often occur in everyday life and cause fatalities. Of course, every road user wants to avoid these accidents, but sometimes these traffic accidents occur due to poor road infrastructure or negligence of the road users themselves. Data from traffic accidents at the Central Lombok District Police, information was obtained that over the last 5 years there has been an increase in the number of traffic accidents.This research was conducted to determine accident-prone locations and prepare a Geographic Information System-based database. From the data from the Central Lombok Police, in the form of accident data for the last 5 years, it was analyzed using a weighting method with the Accident Equivalent Number parameters and the Upper Control Limit method so that a Geographic Information System-based accident-prone location database program was compiled in Central Lombok Regency.The results of the analysis and database preparation showed that accident-prone locations in Central Lombok Regency are located on the BIL Bypass road, Praya-Mantang Highway and Mataram-Sikur Highway, which are dominated by the front-on collision type with the highest age of accident victims aged 16-30. years with 66.4% male and 33.6% female. The highest number of accidents occurs in the morning and the highest in sunny weather at 95.5%. By determining the location of these accident-prone areas, it is hoped that this can provide information in decision making for policy holders to reduce the number of accidents in Central Lombok Regency.